Emergency-Use Vaccine Mandates and Bodily Integrity: Assessing the Validity of Proportionality Test in Legal Frameworks - Khalil, Eman Hussien (AUC Knowledge Fountain, 2026)
Courts confronting emergency-use vaccine mandates during pandemics have revealed that existing legal frameworks are not equipped to handle the emergency context, as seen in their inconsistent description of government measures and their limited capacity to integrate evolving scientific developments on EUA vaccines into proportionality analysis. This thesis argues that when mandates concern Emergency Use Authorized COVID-19 vaccines, courts must abandon the formalistic distinction between “mandatory” and “compulsory” measures and instead focus on whether the practical consequences of non-compliance remove an individual’s genuine choice; where they do, the measure is coercive in substance and triggers the examination of proportionality. Drawing on comparative jurisprudence in the United States, the European Court of Human Rights, the Court of Justice of the European Union, and selected common-law decisions, the thesis shows that judicial reliance on police powers and deferential reasonableness review has allowed courts to sidestep structured proportionality, particularly the demanding scrutiny inherent in suitability, necessity, and strict proportionality tests. It further contends that proportionality, despite its own indeterminacy and susceptibility to judicial discretion, remains the most appropriate framework for evaluating EUA mandates if courts treat scientific evidence as dynamic and central at every stage, require governments to justify mandates against less intrusive alternatives with contemporaneous data, and make explicit the evidentiary basis of their balancing. Normatively, the thesis calls for evidence-driven proportionality analysis that both recognizes the coercive reality of “soft” mandates and insists on heightened judicial transparency, thereby strengthening the protection of bodily integrity without disabling legitimate emergency public health responses.